2018
DOI: 10.1126/scitranslmed.aam8604
|View full text |Cite
|
Sign up to set email alerts
|

Transgelin-2 as a therapeutic target for asthmatic pulmonary resistance

Abstract: There is a clinical need for new bronchodilator drugs in asthma, because more than half of asthmatic patients do not receive adequate control with current available treatments. We report that inhibition of metallothionein-2 protein expression in lung tissues causes the increase of pulmonary resistance. Conversely, metallothionein-2 protein is more effective than β-agonists in reducing pulmonary resistance in rodent asthma models, alleviating tension in tracheal spirals, and relaxing airway smooth muscle cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(70 citation statements)
references
References 61 publications
2
64
0
3
Order By: Relevance
“…The deleterious impact of transgelin‐2‐overexpressing cytotoxic T cells is not expected because of its endogenous nature in T cells, which has not been reported thus far. Notably, transgelin‐2 has been suggested as a promising antasthmatic drug target in a recent study; its agonist, TSG12, relaxes both human and mice airway smooth muscle cells and reduces pulmonary resistance without detectable toxicity or desensitization . Taken together, transgelin‐2‐mediated actin and LFA‐1‐ICAM‐1 axis concurrent enhancement may be a safe and potential supplementary regime for conventional cell‐mediated cancer immunotherapies.…”
Section: Resultsmentioning
confidence: 99%
“…The deleterious impact of transgelin‐2‐overexpressing cytotoxic T cells is not expected because of its endogenous nature in T cells, which has not been reported thus far. Notably, transgelin‐2 has been suggested as a promising antasthmatic drug target in a recent study; its agonist, TSG12, relaxes both human and mice airway smooth muscle cells and reduces pulmonary resistance without detectable toxicity or desensitization . Taken together, transgelin‐2‐mediated actin and LFA‐1‐ICAM‐1 axis concurrent enhancement may be a safe and potential supplementary regime for conventional cell‐mediated cancer immunotherapies.…”
Section: Resultsmentioning
confidence: 99%
“…The vessel/airway wall undergoes significant pathological changes in the smooth muscle 1 and in the extracellular matrix (ECM) that surrounds and supports the cells 2,3 with the onset of disease. The search for mechanisms that underlie the development of these diseases and the search for novel therapies has largely focused on the smooth muscle cells (SMCs) 4,5 , as they are the primary effectors of constriction. The pathological changes in the ECM 2,6 , on the other hand, have not received much attention.…”
Section: Introductionmentioning
confidence: 99%
“…Whether this represents a potential therapeutic target requires further study. Animal studies have demonstrated that Metallothionein-2 (MT-2) can relax ASM and reduce pulmonary resistance via transgelin-2 (TG2) 49 . In vitro, treatment of human ASM cells with the specific TG2 agonist, TSG12, reduced resistance more effectively than β 2 -agonists and may represent a further target for smooth muscle dysfunction in asthma.…”
Section: Beyond T2 Inflammation: Mechanisms and Potential Therapiesmentioning
confidence: 99%